Activation energy impact in nonlinear radiative stagnation point flow of Cross nanofluid. (February 2018) - Khan, Muhammad Ijaz; Hayat, Tasawar; Khan, Muhammad Imran; Alsaedi, Ahmed
Abstract: Here modeling and computations are presented to introduce the novel concept of activation energy in mixed convective magnetohydrodynamic (MHD) stagnation point flow towards a stretching surface. Chemical reaction at the surface is implemented. Nanofluid aspects for thermophoresis and Brownian motion have been considered. Nonlinear thermal radiation and heat absorption/generation are presented. Nonlinear computations have been presented using Runge–Kutta–Fehlberg (RKF) Numerical Method. Main focus in this study for the description of velocity, temperature and nanoparticle concentration. Skin friction coefficient, Nusselt and Sherwood numbers are computed and discussed in Tables. Our investigations reveal that species concentration enhances for higher estimation of activation energy variable. Nusselt and Sherwood numbers show similar behavior for rising values of Weissenberg number.